The Emerging Adulthood Period for Students: Anxiety about the Future, Subjective Welfare, and Islamic Religiosity/ Masa Emerging Adulthood pada Mahasiswa: Kecemasan akan Masa Depan, Kesejahteraan Subjektif, dan Religiusitas Islam - Qolbi, Fera Hayatun; Musthofa, Ariez; Chotidjah, Sitti (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2020)
This study aims to report about the effect of future anxiety on the subjective well-being of emerging adulthood with religiosity as a moderator for students at the Universitas Pendidikan Indonesia Bumi Siliwangi. This research uses a quantitative approach with a moderated causal method. The sample in this study was 300 final-year students at Universitas Pendidikan Indonesia. The sampling technique in this study uses accidental sampling. The instruments used are Future Anxiety Measurement, Satisfaction with life, Positive and Negative Affect Schedule (HEAT), Centrality of Religiosity Scale (CRS), Muslim Religiosity Scale (MRS), and A Psychological Measure of Islamic Religiousness. The analysis technique used is a simple regression and Moderated Regression Analyze (MRA). The results showed that the moderator variable of religiosity showed insignificant results. So it can be said that religiosity cannot moderate the influence of anxiety about the future on subjective well-being at the final year students of Universitas Pendidikan Indonesia. Copyright © 2020. Psikoislamika: Jurnal Psikologi dan Psikologi Islam